Atitudes de docentes sobre o ensino de língua portuguesa em escolas do campo: considerações sobre a pedagogia da variação linguística - Basso, Izabella Regina (2024)
This research aimed to identify language attitudes expressed by Portuguese teachers who work in country schools located in the West and Northwest of Paraná. We proposed the following research questions: i) What knowledge, beliefs and assessments are triggered by Portuguese teachers from country schools regarding the sociolinguistic reality of the community, language variation and the teaching of Portuguese?; ii) What tendencies of action or effective actions do the teachers who are subjects of research develop from the perspective of the pedagogy of linguistic variation? Based on these questions, we formulated the following hypotheses: 1) The knowledge, beliefs and assessments triggered by teachers may be related to the schooled view of the language, linked to the notion of prestige of the standard norm in relation to the variants in the community; 2) The action tendencies or effective actions of teachers may be closely related to the knowledge, beliefs and assessments that they express as teachers. The theoretical framework include discussions on the concepts of language and language variation, based on authors such as Calvet (2002), Tarallo (2005), Bagno (2007; 2008), Labov (2008), Faraco (2008), Cavalcanti (2015) and Faraco (2015); language attitudes, based on authors such as Lambert e Lambert (1968), Bem (1973) and Moreno Fernández (2009), in addition to the concepts of stereotype, prejudice and stigma, based on authors such as Goffman (1988), Bagno (1999) and Botassini (2013); and the pedagogy of language variation, based on Bortoni-Ricardo (2004; 2005), Faraco (2008; 2015), Mollica (2010) and Faraco (2015). The methodology used is characterized as qualitative – although we use some percentage data –, of an interpretative nature, as it allows a look at attitudes emanating from the work of teachers in teaching Portuguese in country schools, given the historical, social and cultural complexity of the linguistic varieties of these communities. The research is based on the corpus composed by data collected through a questionary applied on-line (Google Forms) to six teachers, in the municipalities of Tupãssi (two schools), Marechal Cândido Rondon (one school) and Quarto Centenário (one school), in the total of four country schools. Based on data from the six teachers, organized into three groups, we analyzed the attitudes they expressed, observing the variables age, years of service and place of work. In the analysis of the first group, we noticed that there may be, in country schools, some difficulties regarding the approach of language variation in the teaching and learning of Portuguese, from the perspective of the pedagogy of language variation. In the second group, we analyzed the cognitive and affective components, linked to teachers’ beliefs and evaluations regarding the teaching of Portuguese and language variation. Finally, in the third group, we examined the conative (attitudinal) component, linked to effective actions or reaction tendencies. The study showed advances in the way of conceiving language, language variation and the teaching of Portuguese, but it also showed the persistence of some beliefs that echo traditional views and practices of language and language teaching. Finally, we highlight that the variables age, years of service and place of work, most of the time, do not seem to be relevant for the expression of beliefs, evaluations and actions (hypothetical or effective ones).